Early initiation of breastfeeding among mothers of children under the age of 24 months in Southern Ethiopia. Issue 1 (December 2016) - Beyene, Misrak; Geda, Nigatu; Habtewold, Tesfa; Assen, Zuriash
Abstract Background The early initiation of breastfeeding (EIBF), or timely initiation of breastfeeding, is the proportion of children put to the breast within one hour of birth. It is an important strategy for reducing perinatal and infant morbidity and mortality, but it remains under practiced in Ethiopia. The aim of the study was to assess the prevalence and the predicting factors associated with EIBF. Methods A community based cross-sectional study was conducted in 634 mothers in Dale Woreda, South Ethiopia. Multistage cluster sampling was used to select participating mothers. EIBF was outcome variable whereas sociodemographic characteristics and knowledge and practice of maternal health service were explanatory variables. A face-to-face interview using a pretested semi-structured questionnaire was done from September 2012 to March 2013. To investigate predicting factors, bivariate and multivariate logistic regression analysis was done. Results A total of 634 mothers of children under 24 months were interviewed. During the time of data collection, 94.3% of the mothers had breastfed. The prevalence of EIBF was 83.7%. Ownership of the house was a significant predicting factor for EIBF. Mothers who lived in rented houses were significantly less likely (60%) to initiate breastfeeding within one hour of birth compared to mothers who owned their own house: Adjusted odds ratio 0.40 (95% Confidence Interval 0.16, 0.97). Conclusion More than three-fourths of mothers initiated breastfeeding within an hour. Findings from our study suggest that improving the mother's socioeconomic status as reflected by house ownership, being a significant predictor of EIBF, would have a central role in improving EIBF.